Poverty assessment in degraded rural drylands in the Monte Desert, Argentina. An evaluation using GIS and Multi-criteria Decision Analysis. - Rubio, María Cecilia (2017)
The work aims to contribute to the construction a local-scale poverty indicator, which contemplates multiple dimensions and allows for spatialization of socioeconomic data for a rural area in the Monte Desert. Given the evident and widely studied relationship between desertification processes and poverty, and aiming to contribute to integrating socioeconomic information to desertification assessment and monitoring, there arises the need for spatializing poverty by addressing its multiple dimensions, aspects poorly developed thus far. For this purpose, a data model was designed, which enabled integrating quantitative and qualitative information within the scope of Geographic Information Systems (GIS) with Multi-criteria Decision Analysis (MCDA), whereby it was possible to spatialize in detail the degree of poverty in the study area, laying the foundations for upscaling the assessment to different scales. This work demonstrates the usefulness of GIS and MCDA as an instrument that enables progressing in new integral, interdisciplinary, multi-scale and multi-temporal approaches.